Cyclicity in Northern Bobwhites: A Time-Analytic Review of the Evidence - Wayne E. Thogmartin; John L. Roseberry; Alan Woolf (National Quail Symposium Proceedings, 2017)
Cyclical behavior in wildlife populations, including northern bobwhite (Colinus virginianus), has long fascinated human observers. However, studies examining cyclicity of bobwhite abundance have yielded contradictory results. We reviewed evidence for periodic fluctuation in bobwhite abundance by studying 73 long-term time series. Our aim was to discern with time-series techniques whether cyclicity occurred in bobwhite abundance. We elucidated the frequency of occurrence, geographical distribution, and potential mechanisms responsible for cyclicity. Approximately one-half (n = 37) of the populations examined demonstrated cyclical behavior, with a period varying between 4 and 17 yrs. True cycles, consistent, significant fluctuations in abundance, were rare, occurring in only 3 time series. The predominant form of periodicity was of the phase-forgetting quasi-cycle type (n = 34). This phase-forgetting may have contributed to previous contradictory findings of cyclicity in this species. We reason cyclicity in bobwhite populations is caused by aperiodic environmental perturbations interacting with density-dependence. Cyclic bobwhite populations occupied the northern and western portion of the species’ range, where stochastic weather events regularly negatively influence bobwhite population dynamics. Bobwhite populations were non-cyclic in the relatively consistent climate of the southeastern United States, however, habitat fragmentation rather than climate may have contributed to the absence of cyclicity in this region.
Keywords: California quail; Callipepla californica; Colinus virginianus; density dependence; environmental forcing; northern bobwhite; periodicity; phase-forgetting quasi-cycles